Temperature-Controlled Bidirectional Enantioselectivity in Asymmetric Hydrogenation Reactions Utilizing Stereodynamic Iridium Complexes - Siebert, Max; Storch, Golo; Rominger, Frank; Trapp, Oliver (Synthesis, 2017)
Stereochemically flexible 2,2(-bis(diphenylphosphino)biphenyl (BIPHEP) ligands were modified with chiral α-substituted carboxylic acid auxiliaries in the 3- and 3′-position. The resulting central-to-axial chirality transfer to the stereochemically flexible chiral axis of the BIPHEP core was investigated as well as complexation of these diastereomeric ligands to iridium(I). Solid-state structures of both ligand diastereomers and a diastereomerically pure iridium(I) BIPHEP complex were obtained. Thermal equilibration of the resulting iridium(I) complexes was studied to investigate the stereodynamic properties of the BIPHEP ligands. The iridium(I) complexes without and after pre-catalysis warming in solution — which induces a shift of the diastereomeric ratio — were applied for asymmetric hydrogenation of a prochiral α-substituted acrylic acid, resulting in temperature-controlled bidirectional enantioselectivity of iridium catalysts for the first time. In both cases, enantioenriched (R)-naproxen as well as (S)-naproxen — after re-equilibration of the catalyst at elevated temperatures — was obtained by using the same catalyst.
Keywords: asymmetric catalysis; bidirectional enantioselectivity; chiral auxiliaries; stereodynamic catalysts; supramolecular chemistry; tropos ligands